1986
DOI: 10.1215/03616878-11-3-367
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Tobacco Products: Issues and Policy Options

Abstract: During the past year, several prominent voluntary health organizations and professional medical associations have called for a ban on all forms of promotion of tobacco products. The proposal raises complex issues, ranging from determination of the effects of tobacco promotion to assessment of the constitutionality of banning advertising of a legal product. We identify the issues that underlie the concern of health professionals, review evidence addressing these issues, and describe and discuss frequently menti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…With many studies finding no significant relationship, and many others finding a significant but generally small relationship, this literature is indeterminate on the issue 70. In any event, technical limitations of the dominant econometric approach71combined with a lack of studies on adolescent smoking make this literature of little utility in trying to assess whether advertising affects smoking by children.…”
Section: Prevention Activitiesmentioning
confidence: 99%
“…With many studies finding no significant relationship, and many others finding a significant but generally small relationship, this literature is indeterminate on the issue 70. In any event, technical limitations of the dominant econometric approach71combined with a lack of studies on adolescent smoking make this literature of little utility in trying to assess whether advertising affects smoking by children.…”
Section: Prevention Activitiesmentioning
confidence: 99%
“…Lancaster & Lancaster (2003a) summarized the studies following this approach. It is disputable, whether such an approach has advantages compared with a direct consideration of a ban's effects (Warner et al 1986). Pollay et al (1996) and Warner et al (1986) indicated that such studies only examine the infl uence of changes in advertising expenditures on the current almost optimal level.…”
Section: Alternative Methodical Approachesmentioning
confidence: 99%
“…It is disputable, whether such an approach has advantages compared with a direct consideration of a ban's effects (Warner et al 1986). Pollay et al (1996) and Warner et al (1986) indicated that such studies only examine the infl uence of changes in advertising expenditures on the current almost optimal level. Increased expenditures on this high level would not affect aggregate consumption signifi cantly -the tobacco companies would otherwise increase their expenditures for advertising.…”
Section: Alternative Methodical Approachesmentioning
confidence: 99%
“…They show steady declines in cigarette smoking prevalence among both male and female seniors from 1977 to 198 1, followed by vacillations in rates and much slower declines for both sexes since that time ( Fig. 3 [35][36][37][38][39][40][41][42][43][44] Age (Years) [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] from these surveys of high school seniors probably underestimate teenage smoking in the general population since they do not include school dropouts; cigarette smoking is inversely related to education and is more common among youth who are not college-b~und. '~~~~ Data from the 198 1 to 1983 Behavioral Risk Factor Surveys conducted by the Centers for Disease Control2' show very high rates of smoking among young white women (about 40% in the age group 18 to 24 years).…”
Section: Teenagersmentioning
confidence: 99%